Research on the Impact of Green Finance Policy on Regional Green Innovation-Based on Evidence From the Pilot Zones for Green Finance Reform and Innovation - Zhang, Chi; Cheng, Xinwei; Ma, Yanyan (Frontiers in Environmental Science, 2022)
To develop green finance and ensure the goal of carbon peaking and carbon neutrality, China set up the pilot zones for green finance reform and innovation in 2017. We empirically tested the policy effect of the pilot zones with data from 2010 to 2019 for prefecture-level cities in China. The study shows that the pilot zones have induced an effect on regional green technology innovation, reflected in the application and acquisition of both green invention patents and green utility patents, and the promotion effect is better for green utility patents than green invention patents, which is supported by the robustness test using PSM-DID. This study provides theoretical support and empirical evidence for evaluating the policy effects of the pilot zones and provides a reference for the differentiated formulation of green financial policies.